Pembuatan dan Implementasi Sistem Akuntansi Penjualan Mini Projie di LED Turbo Mojokerto - Susilo, Cynthia Adelina; Permatasari, Anita (-, 2025)
With developments in automotive technology, headlamps also continue to experience innovation. Retrofit modification is a modification made to the lighting sector, whether motorbike or car, which is felt to be less bright by adding a projector (projie) or BiLED which is installed in the car's headlamp or foglamp, while the mini projector will generally be installed in the car grill. The purpose of this writing is to determine whether the sales accounting system and installation of the mini project on the grill are in accordance with the elements of the sales accounting system. The limitation of writing is that the author only examines the suitability of sales accounting elements and the installation of mini projects in car grills on Turbo LEDs in Mojokerto City, East Java. Implementation of mentoring activities is carried out in several stages. These stages are conducting a survey of the existing system, identifying the information needed, identifying system requirements and compiling a system analysis report. In conclusion, LED Turbo still uses a manual system, namely the transaction process still uses a manual system, daily recording is carried out in the cash sales accounting system in the shop it is still not optimal and simple, and there are no recordings in general journals and in terms of accounting records related to the sales accounting system, the accounting records are incomplete